FENOMENA POLITIK UANG DALAM PILKADA - Fitriyah, Dra. Fitriyah, MA (Politika: Jurnal Ilmu Politik, 2012)
Money politics happens in districts and provinces head local elections. The regulation (Law Number 32 of 2004) is not sufficiently strong in regulating money politics and providing sanctions on the money politics,  beside the problem is also on the law enforcement itself. This activity (money politics) threatens not only clean and effective governance but also clean and honest elections.  Those who spend money politics  to win elections are normally expected to recover after elections their investment with a profit. If unchecked, the defense of public interests and the common weal may be on the retreat. These are crimes, and seriously undermine the integrity of elections. We need law making bodies are pay attention how to  enforce controls on money politics. In this case, The Draft which regulated head local elections relevant to push on eradicating and controlling money politics.   Keywords :   money politics, head local elections